The History of Armand Trousseau and Cancer-Associated Thrombosis - Metharom, Pat; Falasca, M.; Berndt, Michael (MDPI AG, 2019)
“Je suis perdu; une phlegmatia qui vient de se déclarer cette nuit, ne me laisse aucun doute sur nature de mon mal.” —Armand Trousseau “I am lost; a phlebitis which has declared itself this night leaves me no doubt about the nature of my illness.”